COVID-19 study on sccientific articles in health communication: A science mapping analysis in Web of Science. - De-las-Heras-Pedrosa, Carlos; Jambrino-Maldonado, Carmen; Rando-Cueto, Dolores; Iglesias-Sánchez, Patricia Pilar (MDPI, 2022)
The COVID-19 pandemic continues to cause a collapse in the health systems and economies of many countries around the world, after 2 years of struggle and with the number of cases still growing exponentially. Health communication has become as essential and necessary for control of the pandemic as epidemiology. This bibliometric analysis identifies existing contributions, jointly studying health communication and the pandemic in scientific journals indexed. A systematic search of the Web of Science was performed, using keywords related to COVID-19 and health communication. Data extracted included the type of study, journal, number of citations, number of authors, country of publication, and study content. As the number of scientific investigations has grown, it is necessary to delve into the areas in which the most impactful publications have been generated. The results show that the scientific community has been quick to react by generating an extraordinary volume of publications. This review provides a comprehensive mapping of contributions to date, showing how research approaches have evolved in parallel with the pandemic. In 2020, concepts related to mental health, mass communication, misinformation and communication risk were more used. In 2021, vaccination, infodemic, risk perception, social distancing and telemedicine were the most prevalent keywords. By highlighting the main topics, authors, manuscripts and journals since the origin of COVID-19, the authors hope to disseminate information that can help researchers to identify subsisting knowledge gaps and a number of future research opportunities.
Keywords: Comunicación en medicina; Riesgos para la salud-Comunicación; COVID-19; Epidemias-Investigación; Información científica y técnica-Métodos matemáticos; Publicaciones científicas-Análisis bibliométrico; Health communication; Coronavirus; COVID-19; Bibliometric analysis